2014
DOI: 10.1007/s00371-014-1052-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual mining of time series using a tubular visualization

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In our recent work [4], we also showed that simple navigation modes can be proposed to the users, thus avoiding the complex problem of 3D navigation. We also underlined that this 3D representation has no occlusion thanks to the tubular shape: it thus resolve another problem in 3D visualizations.…”
Section: B Tubular Representations For Time-dependent Datamentioning
confidence: 96%
See 2 more Smart Citations
“…In our recent work [4], we also showed that simple navigation modes can be proposed to the users, thus avoiding the complex problem of 3D navigation. We also underlined that this 3D representation has no occlusion thanks to the tubular shape: it thus resolve another problem in 3D visualizations.…”
Section: B Tubular Representations For Time-dependent Datamentioning
confidence: 96%
“…Recently, we extended DataTube to DataTube2, with various visualization modes and interactions that are devoted to sequence mining [4]. However, DataTube2 is not adapted to the mining of software logs, because it does not represent important information such as the messages or the synchronization between threads or other software objects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternative spatial layouts can reveal periodic structure [39] and accentuate interesting data regions [15]. Visualizations have been applied to the result of pattern discovery algorithms, including wavelet analysis [18], cluster analysis across multiple time scales [40], motif discovery with augmented suffix trees [24], tabular views [6] and frequently occurring patterns using k-means clustering [16]. We find no work on the interactive classification of time series data.…”
Section: Visual Pattern Discovery In Time Seriesmentioning
confidence: 99%